Biocultural evolution as seen in the light of results and interpretations of molecular biology - Schramm, Ryszard W. (Anthropological Review, 1978)
An opinion of a molecular and theoretical biologist on the problem of biocultural evolution of mankind is presented. Starting from the principal elementary theories as well as from the fundamental features of living systems, the hierarchy of biological systems and the role of different kinds of information in their formation are discussed. The biological phenomenon originates on the individual level, and only in the species Homo sapiens for the formation of the phenomenon a social group and level is necessary. From the molecular point of view, no basis exists for distinguishing Man from other species. The essential difference is connected with information and organization of the system. The need for different kinds of information and the superior role of the outside information over the molecular, genetic, for the occurrence of the phenomenon of bioculture, are presented. This, together with the process of cephalization, accelerates enormously the evolution of the Homo species and has been the origin of bioculture as well as the cause of its evolution.